Síntese e caracterização de novos derivados da adenina com potencial atividade antibacteriana - Javarini, Clara Lirian (2022)
The literature reveals a large number of drugs that are derived from purine or pyrimidine bases. In particular, adenine derivatives have been synthesized and studied by scientists around the world, due to the numerous biological and pharmacological properties that these structures can present. In view of the promising results, studies related to these analogues are increasing, which, when incorporated into other biologically active molecules, can extend the spectrum of activities and increase the efficiency of drugs. Therefore, this work addresses the synthesis and characterization of new adenine derivatives aiming at a potential antibacterial activity for these compounds. For this, an alkynyl-adenine derivative was initially prepared via bimolecular nucleophilic substitution (SN2), using adenine and propargyl bromide. The product formed served as a precursor for the synthesis of eight new adenine derivatives containing the 1,2,3-triazole ring, obtained from the 1,3-dipolar cycloaddition of Huisgen, using several azides functionalized in the presence of Cu(I) as a catalyst. All products were obtained with yields ranging from 75% to 99%, and were fully characterized by NMR and Infrared spectroscopy and mass spectrometry techniques. The derivatives prepared were targets of studies of antibacterial activity against strains of Staphylococcus aureus, Escherichia coli and Staphylococcus epidermidis. For this, disc diffusion and broth microdilution methods were used, revealing good results for two of the adenine derivatives tested against the bacterium Staphylococcus epidermidis